Liver-specific gene expression: A-activator-binding site, a promoter module present in vitellogenin and acute-phase genes. - Kaling, M (1991)
The A2 vitellogenin gene of Xenopus laevis, which is expressed liver specifically, contains an A-activator-binding site (AABS) that mediates high in vitro transcriptional activity in rat liver nuclear extracts. Footprint experiments with DNase I and gel retardation assays revealed the binding of several proteins to AABS. Using binding sites of known DNA-binding proteins as competitors in the gel retardation assay, we found that the transcription factor C/EBP and/or one of its "iso-binders" as well as LFB1/HNF1 bound AABS. These interactions were confirmed by in vitro transcription experiments using various oligonucleotides as competitors. However, saturating amounts of C/EBP- and LFB1/HNF1-binding sites as competitors only partially blocked AABS-mediated transcriptional activity. This finding implies that at least a third distinct transcription factor interacts with AABS. In vitro transcription experiments revealed that AABS was present not only in the closely related Xenopus A1 vitellogenin gene but also in acute-phase genes as a liver-specific regulatory element known to confer the interleukin-6 response. Both AABS and the interleukin-6 response element are promoter modules interacting with at least three distinct transcription factors, including C/EBP and LFB1/HNF1.